If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) = -3x + 42 Reorder the terms: 6(-2 + x) = -3x + 42 (-2 * 6 + x * 6) = -3x + 42 (-12 + 6x) = -3x + 42 Reorder the terms: -12 + 6x = 42 + -3x Solving -12 + 6x = 42 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -12 + 6x + 3x = 42 + -3x + 3x Combine like terms: 6x + 3x = 9x -12 + 9x = 42 + -3x + 3x Combine like terms: -3x + 3x = 0 -12 + 9x = 42 + 0 -12 + 9x = 42 Add '12' to each side of the equation. -12 + 12 + 9x = 42 + 12 Combine like terms: -12 + 12 = 0 0 + 9x = 42 + 12 9x = 42 + 12 Combine like terms: 42 + 12 = 54 9x = 54 Divide each side by '9'. x = 6 Simplifying x = 6
| 2+4x=x+11 | | 5x-3(x-1)-7=2(x-2) | | 4t+9+(2t+7)= | | -6=6+k | | -3(x-4)+7=-2x | | (4x^2-3x)(6x+5)=0 | | 3x-25=11x-5+2x | | 5(x-3)=2x+21 | | 5y+2x=25 | | 26+4y-4=16y-13-5y | | 3x-0.25y=-2 | | x+0.20(3)=0.60(x+3) | | 22x+8-24x=7-9 | | 6-(5p+3)=6[(5p-3)-(p-7)] | | -4x+16=-11x+10 | | 10x+9-9x=15 | | x=-14-3x | | -10+18=m-9 | | -15=5(3q-10) | | -3x-5=5+2x | | -3t-4=7 | | -8x+10=-x+80 | | 7x=-47 | | 3(6+8R)-3(R+2)= | | 4k^2+26k-36=0 | | -5=x-9 | | 4(x+8)=-4(x-16) | | -0.01x^2+0.92x=0 | | 5e+10=25 | | -6=n+2+7n | | 3x+2x+3+3x+2x+3=5x-3+5x-3+5x-3 | | x+4/2=5/2-x-1/5 |